Pioneering Firms in Fragile and Conflict-Affected States Why and How Development Finance Institutions Should Support Them - Collier, Paul (World Bank E-Library Archive, 2019)
The role of 'first movers' in fragile states is critical: they grow and diversify markets in ways that no other firms do, generating disproportionate impact in terms of development and stability. But pioneer firms are rare in fragile states. This study documents their profile, their challenges, and the barriers that prevent them from realizing their potential. The study also explores the rationale for development finance institutions to support them, and proposes new ways to offset costs, risks, and the 'unknown unknowns' that generate radical uncertainty. Through a process of social learning and resetting negative self-fulfilling investor narratives, development finance institutions can help pioneering firms shift the growth trajectory of fragile and conflict-affected states